Caterpillars suppress nocifensive behaviours during the quiescent 'sphinx' state - Kondakath, Gayathri; Messinger, Isabel; Veliko-Shapko, Annushka; Trimmer, Barry (Tufts University Tisch Library, 2026)
Noxious (harmful) stimuli are detected by a specialized sensory process known as nociception, which typically evokes defensive behaviours to minimize tissue damage. While sensitization of nocifensive responses by intense or repetitive stimuli is well-documented in insects, instances of deliberate nociceptive suppression are relatively unexplored, particularly within natural behavioural contexts. Here, we describe a behavioural state in the tobacco hornworm (Manduca sexta), termed the 'sphinx' state, characterized by a distinct ventrally curled posture of the head and thorax following gentle disturbance. One of the striking characteristics of this state is that the larvae exhibit reduced responsiveness to noxious stimuli, indicating nociceptive down regulation. We also observe an overall reduced behavioural responsiveness to innocuous stimuli. Our surgical experiments show that the cerebral ganglion is essential to initiate the sphinx state. Overall, this discovery reveals a novel instance of active behavioural modulation in insects and highlights the flexibility of nociceptive responses, challenging the notion of nociception as strictly hard-wired and stereotyped.; Keywords: nociceptive modulation, Manduca sexta, insect larvae, defensive posture, nociceptive tolerance.